Regional unemployment in Argentina - Galiani, Sebastián (1999)
The study of regional unemployment arises two very important issues. First, it is entirely relevant to establish the degree of persistence of both the regional structure of unemployment itself and the persistence of shocks at the regional level. The second interesting issue is the determinants of equilibrium regional unemployment. What makes a region to have a higher equilibrium unemployment rate than other regions? In this paper, we adress these issues. (Párrafo extraído del texto a modo de resumen)